Kegiatan Kompetisi Olahraga Mahasiswa Antar Fakultas Sportavest 2023 untuk Pemberdayaan UMKM di Kelurahan Pondok Labu - Amrullah, Afif Amir; Arbitera, Cahya (Jurnal Bisnis Indonesia, 2024)
One of the tridharmas goals for higher education is the existence of a campus can provide benefitsand prosperity to society. After the Covid-19 pandemic, there was a slowdown in people's economicactivities, marked by a large number of unemployed people and a decrease in purchasing power, aswell as a reduction in the income of MSMEs (UMKM) in the area around the UPN Veteran Jakartacampus. If this condition remain ignored, it will lead to a negative impact and reduce social relationsbetween campus residents and surrounding residents. Because efforts are needed to improve campusrelations with local residents while empowering the economy through Sportavest 2023 activities. Thisresearch contains service activities regarding empowering community MSMEs in Pondok LabuSubdistrict to be able to promote their products widely and increase income from product sales whichsynergized with sports activities from student.Keywords: Students; Sportavest; MEMEs